Methylphenidate without Sleep Problems - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The effects of methylphenidate (MPH) administered at 4 PM on behavior and sleep in 12 child psychiatric inpatients with ADHD were evaluated in a double-blind, crossover study at the Division of Child and Adolescent Psychiatry, Long Island Jewish Medical Center, New Hyde Park, NY.